Bright silver-based quaternary nanostructures
By preparing the nanostructures of the cores of Ag, In, Ga and S and the shells of Ag, Ga and S, the problems of insufficient band-side emission and defect emission in the prior art are solved, and high quantum yield and narrow half-maximum full-scale Wide photoluminescent properties.
Patent Information
- Application Number
- CN202211320034.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-25
- Filing Date
- 2020-06-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-06-18
AI Technical Summary
It is difficult to prepare Ag-In-Ga-S nanostructures with extremely high band-side emission, narrow half-maximum full width and high quantum yield in the prior art, and defect emission exists, affecting photoluminescence performance.
Using nanostructures containing cores of Ag, In, Ga and S and shells of Ag, Ga and S, nanostructures with peak emission wavelengths between 480-545 nm, with at least 80% emissions being prepared by specific heat treatment and reaction conditions. It is a band-side emission and achieves a quantum yield of 80-99.9%.
The band-side emission percentage and quantum yield of nanostructures have been successfully improved, defect emission has been reduced, and photoluminescence performance has been significantly improved.
Smart Images

Figure CN115678542B_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese invention patent application No. 202080036773.9, with an application date of June 18, 2020 and an invention name of “Quaternary Nanostructure Based on Bright Silver”. Technical Field
[0002] The present invention relates to the field of nanotechnology. More specifically, the present invention provides a nanostructure having a core comprising Ag, In, Ga and S (AIGS) and a shell comprising Ag, Ga and S (AGS), wherein the peak emission wavelength (PWL) of the nanostructure is 480-545 nm, and wherein at least about 80% of the emission is band edge emission. The present disclosure also provides a method for preparing the AIGS / AGS core-shell nanostructure. Background Art
[0003] Nanostructures containing Group I-III-VI semiconductors are promising candidates for non-toxic fluorescent materials. Uematsu et al., NPG Asia Materials 10:713-726 (2018) disclosed AgInS2 / GaS x Core / shell nanostructures, where x ranges from 0.8 to 1.5. These core / shell nanostructures exhibit band edge emission and broad, red-shifted defect emission. The reduction of defect emission is obtained by using 1,3-dimethylthiourea (as a sulfur source) and Ga(acac)3 to produce GaS and modifying the shell procedure using a temperature gradient reaction. However, the band edge emission is red-shifted and the defect emission persists.
[0004] Kameyama et al., ACS Appl. Mater. Interfaces 10:42844-42855 (2018) disclosed Ag-In-Ga-S (AIGS) nanostructures with significant defect emission. Defect emission is achieved by applying GaS x However, the defect emission remains at about 15% of the band edge emission intensity and the photoluminescence quantum yield is low (<30%).
[0005] There remains a need in the art for AIGS nanostructures with extremely high band edge emission (BE), narrow full width at half maximum (FWHM), high quantum yield (QY), and reduced red shift. Summary of the invention
[0006] The present invention provides a nanostructure comprising a core comprising Ag, In, Ga and S (AIGS) and a shell comprising Ag, Ga and S (AGS), wherein the nanostructure has a peak emission wavelength (PWL) in the range of 480-545 nm and wherein at least about 80% of the emission is band-edge emission, and wherein the nanostructure exhibits a quantum yield (QY) of 80-99.9%.
[0007] In some embodiments, the FWHM of the emission spectrum of the nanostructure is less than 40 nm. In some embodiments, the FWHM of the emission spectrum of the nanostructure is 36-38 nm.
[0008] In some embodiments, the nanostructures have a QY of 82-96%. In some embodiments, the nanostructures have a QY in the inclusive range of 85-95%. In some embodiments, the nanostructures have a QY of 86-94%.
[0009] In some embodiments, the OD of the nanostructure 450 / Mass (mL mg-1cm -1 ) is greater than or equal to 0.8. In some embodiments, the OD of the nanostructure 450 / Mass (mL mg-1cm -1 ) is within the inclusive range of 0.8-2.5. In some embodiments, the OD of the nanostructures 450 / Mass (mL mg-1cm -1 ) is within the inclusive range of 0.87-1.9.
[0010] In some embodiments, the nanostructures have an average diameter of less than 10 nm by TEM. In some embodiments, the average diameter is about 5 nm.
[0011] In some embodiments, at least about 80% of the emission is band-edge emission. In some embodiments, at least about 90% of the emission is band-edge emission.
[0012] In some embodiments, the nanostructures are quantum dots.
[0013] The present invention also provides a nanostructured composition comprising:
[0014] (a) a population of at least one nanostructure as described herein, and
[0015] (b) at least one organic resin.
[0016] In some embodiments, the nanostructure composition comprises at least one second population of nanostructures having a PWL greater than 545 nm.
[0017] The present invention also provides a method for preparing the nanostructure composition described herein, the method comprising:
[0018] (a) providing a population of at least one nanostructure as described herein; and
[0019] (b) mixing at least one organic resin with at least one population of (a).
[0020] In some embodiments, at least about 80% of the emission is band-edge emission. In some embodiments, at least about 90% of the emission is band-edge emission.
[0021] The present invention also provides a device comprising the composition described herein.
[0022] The present invention also provides a film comprising the composition described herein, wherein the nanostructures are embedded in a matrix comprising the film.
[0023] The present invention also provides a nanostructured molded article, comprising:
[0024] (a) a first conductive layer;
[0025] (b) a second conductive layer; and
[0026] (c) a nanostructured layer between the first conductive layer and the second conductive layer, wherein the nanostructured layer comprises a composition described herein.
[0027] The present invention also provides a method for preparing the core / shell nanostructure described herein, comprising:
[0028] (a) preparing a mixture comprising Ag-In-Ga-S (AIGS) cores, a sulfur source and a ligand;
[0029] (b) adding the mixture obtained in (a) to a mixture of gallium carboxylate and ligand at a temperature of 180-300° C.;
[0030] (c) maintaining the temperature in the range of 180-300° C. for 5-300 minutes; and
[0031] (d) separating the nanostructures.
[0032] In some embodiments, the ligand in (a) and (b) is an alkylamine. In some embodiments, the alkylamine is oleylamine.
[0033] In some embodiments, the sulfur source is derived from S8.
[0034] In some embodiments, the temperature in (a) and (b) is about 270°C.
[0035] In some embodiments, the mixture in (b) further comprises a solvent. In some embodiments, the solvent is octadecene, dibenzyl ether, or squalane.
[0036] In some embodiments, the ratio of gallium carboxylate to AIGS cores is 0.008-0.2 mmol of gallium carboxylate / mg of AIGS.
[0037] In some embodiments, at least about 80% of the emission is band-edge emission. In some embodiments, at least about 90% of the emission is band-edge emission.
[0038] The present invention also provides a method for preparing the nanostructure described herein, comprising:
[0039] (a) preparing a mixture comprising Ag-In-Ga-S (AIGS) cores and a gallium halide in a solvent and maintaining the mixture for a time sufficient to obtain AIGS nanostructures having a PWL of 480-545 nm, and wherein at least about 60% of the emission is band edge emission, and
[0040] (b) separating the nanostructures.
[0041] In some embodiments, the gallium halide is gallium iodide.
[0042] In some embodiments, the solvent comprises trioctylphosphine.In some embodiments, the solvent comprises toluene.
[0043] In some embodiments, the sufficient time in (a) is 1 to 200 hours. In some embodiments, the sufficient time is about 20 hours.
[0044] In some embodiments, the mixture is maintained at 20-100° C. In some embodiments, the mixture is maintained at about room temperature.
[0045] In some embodiments, the molar ratio of gallium halide to AIGS core is from about 0.1 to about 30.
[0046] The present invention also provides a method for preparing the core / shell nanostructure described herein, comprising:
[0047] (a) preparing a mixture comprising Ag-In-Ga-S (AIGS) core, a sulfur source, a ligand and a gallium halide at 180-300° C.;
[0048] (b) maintaining the temperature in the range of 180-300° C. for 5-300 minutes; and
[0049] (c) separating the nanostructures.
[0050] In some embodiments, the ligand in (a) is an alkylamine. In some embodiments, the alkylamine is oleylamine.
[0051] In some embodiments, the sulfur source is derived from S8.
[0052] In some embodiments, the temperature in (a) and (b) is about 240°C.
[0053] In some embodiments, the mixture in (b) further comprises a solvent. In some embodiments, the solvent is octadecene, dibenzyl ether, or squalane.
[0054] In some embodiments, the ratio of gallium halide to AIGS cores is 0.008-0.2 mmol of gallium carboxylate / mg of AIGS.
[0055] In some embodiments, at least about 80% of the emission is band-edge emission. In some embodiments, at least about 90% of the emission is band-edge emission.
[0056] The present invention also provides a method for preparing AIGS / AGS core-shell nanostructures, which unexpectedly have very high band edge emission (>90%) and very high quantum yield (80-99%). The method comprises:
[0057] (a) reacting Ga(acetylacetonate) 3 , InCl 3 and a ligand, optionally in a solvent, at a temperature sufficient to obtain an In-Ga reagent, and
[0058] (b) reacting the In-Ga reagent with the Ag2S nanostructure at a temperature sufficient to produce the AIGS nanostructure,
[0059] (c) reacting the AIGS nanostructures with an oxygen-free Ga salt in a solvent containing a ligand at a temperature sufficient to form an AIGS / AGS core-shell nanostructure.
[0060] In some embodiments, the ligand is an alkylamine. In some embodiments, the alkylamine is oleylamine. In some embodiments, the ligand acts as a solvent and does not require a second solvent. In some embodiments, the solvent is present in the reaction mixture. In some embodiments, the solvent is a high boiling point solvent, such as octadecene, squalane, dibenzyl ether or xylene. In some embodiments, the sufficient temperature in (a) is 100-280°C; the sufficient temperature in (b) is 150-260°C; and the sufficient temperature in (c) is 170-280°C. In some embodiments, the sufficient temperature in (a) is about 210°C; the sufficient temperature in (b) is about 210°C; and the sufficient temperature in (c) is about 240°C.
[0061] In some embodiments, the ligand is bound to the core-shell nanostructure. In some embodiments, the ligand is a silane. In some embodiments, the silane is an aminoalkyltrialkoxysilane or a thioalkyltrialkoxysilane. In some embodiments, the aminoalkyltrialkoxysilane is 3-aminopropyl)triethoxysilane or 3-mercaptopropyl)triethoxysilane.
[0062] The present invention also provides core-shell nanostructures with silane ligands attached to a substrate. In some embodiments, the substrate is glass. In some embodiments, the glass is part of a quantum dot color conversion film. In some embodiments, the quantum dot color converter comprises
[0063] back plane;
[0064] A display panel is disposed on the back panel; and
[0065] The quantum dot layer including the nanostructure is arranged on the display panel.
[0066] In some embodiments, the quantum dot layer comprises a patterned quantum dot layer. In some embodiments, the backplane comprises an LED, an LCD, an OLED, or a microLED.
[0067] In particular, this application relates to the following:
[0068] 1. A nanostructure comprising Ag, In, Ga, and S (AIGS) and a shell comprising Ag, Ga, and S (AGS), wherein the nanostructure has a peak emission wavelength (PWL) of 480-545 nm and wherein at least about 80% of the emission is band edge emission, and wherein the nanostructure exhibits a quantum yield (QY) of 80-99.9%.
[0069] 2. The nanostructure according to item 1, wherein the FWHM of the emission spectrum of the nanostructure is less than 40 nm.
[0070] 3. The nanostructure according to item 2, wherein the FWHM of the emission spectrum of the nanostructure is 36-38 nm.
[0071] 4. The nanostructure according to any one of items 1 to 3, wherein the QY of the nanostructure is 82-96%.
[0072] 5. The nanostructure according to item 4, wherein the QY of the nanostructure is 85-95%.
[0073] 6. The nanostructure according to any one of items 1 to 4, wherein the QY of the nanostructure is 86-94%.
[0074] 7. A nanostructure according to any one of items 1 to 6, wherein the OD of the nanostructure 450 / Mass (mLmg -1 cm -1 ) is greater than or equal to 0.8.
[0075] 8. The nanostructure according to item 7, wherein the OD of the nanostructure 450 / Mass (mL mg -1 cm -1 ) is within the inclusive range of 0.8-2.5.
[0076] 9. The nanostructure according to item 8, wherein the OD of the nanostructure 450 / Mass (mL mg -1 cm -1 ) is within the inclusive range of 0.87-1.9.
[0077] 10. The nanostructure according to any one of items 1 to 9, wherein the average diameter of the nanostructure is less than 10 nm according to TEM.
[0078] 11. The nanostructure according to item 10, wherein the average diameter is about 5 nm.
[0079] 12. The nanostructure of any one of items 1-11, wherein at least about 80% of the emission is band-edge emission.
[0080] 13. The nanostructure of any one of items 1-12, wherein at least about 90% of the emission is band-edge emission.
[0081] 14. The nanostructure according to item 13, wherein 92-98% of the emission is band-edge emission.
[0082] 15. The nanostructure according to item 13, wherein 93-96% of the emission is band-edge emission.
[0083] 16. The nanostructure according to any one of items 1 to 15, which is a quantum dot.
[0084] 17. A nanostructured composition comprising:
[0085] (a) at least one population of nanostructures according to any one of items 1 to 16, and
[0086] (b) at least one organic resin.
[0087] 18. The nanostructure composition according to item 17, further comprising at least one second population of nanostructures having a PWL greater than 545 nm.
[0088] 19. A method for preparing the nanostructure composition of item 17, the method comprising:
[0089] (a) providing a population of at least one nanostructure according to any one of items 1 to 16; and
[0090] (b) mixing at least one organic resin with the at least one population of (a).
[0091] 20. The method of item 19, wherein 92-98% of the emission is band-edge emission.
[0092] 21. The method of item 19, wherein 93-96% of the emission is band edge emission.
[0093] 22. A device comprising the composition of any one of items 17 and 18.
[0094] 23. A film comprising the composition of any one of items 17 and 18, wherein the nanostructures are embedded in a matrix comprising the film.
[0095] 24. A nanostructured molded article comprising:
[0096] (a) a first conductive layer;
[0097] (b) a second conductive layer; and
[0098] (c) a nanostructure layer between the first conductive layer and the second conductive layer,
[0099] Wherein, the nanostructure layer comprises the composition described in any one of items 17 and 18.
[0100] 25. A method for preparing the nanostructure according to any one of items 1 to 16, comprising:
[0101] (a) reacting Ga(acetylacetonate) 3 , InCl 3 and a ligand, optionally in a solvent, at a temperature sufficient to obtain an In-Ga reagent, and
[0102] (b) reacting the In-Ga reagent with the Ag2S nanostructure at a temperature sufficient to form the AIGS nanostructure,
[0103] (c) reacting the AIGS nanostructures with an oxygen-free Ga salt in a solvent containing a ligand at a temperature sufficient to form an AIGS / AGS core-shell nanostructure.
[0104] 26. The method according to item 25, wherein the ligand is an alkylamine.
[0105] 27. The method according to item 26, wherein the alkylamine is oleylamine.
[0106] 28. The method according to any one of items 25-27, wherein the optional solvent is octadecene, squalane, dibenzyl ether or xylene.
[0107] 29. The method according to any one of items 25-28, wherein the temperature sufficient in (a) is 100-280°C; the temperature sufficient in (b) is 150-260°C; and the temperature sufficient in (c) is 170-280°C.
[0108] 30. The method of any one of items 25-28, wherein the temperature sufficient in (a) is about 210°C; the temperature sufficient in (b) is about 210°C; and the temperature sufficient in (c) is about 240°C.
[0109] 31. The nanostructure according to any one of items 1-16, further comprising a ligand bound to the nanostructure.
[0110] 32. The nanostructure according to item 31, wherein the ligand is a silane.
[0111] 33. The nanostructure according to item 32, wherein the silane is an aminoalkyltrialkoxysilane.
[0112] 34. The nanostructure according to item 33, wherein the aminoalkyltrialkoxysilane is (3-aminopropyl)triethoxysilane.
[0113] 35. The nanostructure according to item 32, wherein the silane is a mercaptoalkyltrialkoxysilane.
[0114] 36. The nanostructure according to item 35, wherein the mercaptoalkyltrialkoxysilane is 3-mercaptopropyltrimethoxysilane.
[0115] 37. The nanostructure according to any one of items 31 to 36, which is adhered to a substrate.
[0116] 38. The nanostructure according to item 37, wherein the substrate is glass.
[0117] 39. The nanostructure of item 38, wherein the glass is part of a quantum dot color conversion film.
[0118] 40. The nanostructure according to item 39, wherein the quantum dot color converter comprises
[0119] Back panel;
[0120] A display panel is disposed on the back panel; and
[0121] A quantum dot layer comprising the nanostructure is disposed on the display panel.
[0122] 41. The nanostructure of item 40, wherein the quantum dot layer comprises a patterned quantum dot layer.
[0123] 42. The nanostructure of item 40, wherein the backplane comprises an LED, an LCD, an OLED, or a microLED. BRIEF DESCRIPTION OF THE DRAWINGS
[0124] Figure 1A and 1B is the absorption spectrum describing the Ag-In-Ga-S (AIGS) core ( Figure 1A ) and photoluminescence spectra ( Figure 1B )’s picture.
[0125] Figure 2 is a transmission electron microscope (TEM) image of an AIGS nucleus.
[0126] Figure 3 is a graph showing the photoluminescence spectra of the starting AIGS core (---) and AIGS core / AGS (Ag-Ga-S) shell (AIGS / AGS) (-) nanostructures.
[0127] Figure 4 is a transmission electron microscopy (TEM) image of AIGS / AGS core / shell nanostructure.
[0128] Figure 5A and 5B Before using GaI3 / trioctylphosphine (TOP) surface treatment ( Figure 5A ) and after ( Figure 5B ). The band edge emission of AIGS nanostructures before surface treatment varies from 513 to 548 nm, and the total quantum yield (QY) (band edge + defect emission) ranges from 5 to 15%. After surface treatment with GaI3 / TOP, the band edge emission contribution is significantly enhanced, while the emission wavelength is maintained and the FWHM is improved (37 to 38 nm).
[0129] Fig. 6A and 6B is obtained by using an oxygenated oleic acid Ga(III) source ( Fig. 6A ) and using an oxygen-free Ga(III) chloride source ( Figure 6B ) TEM images of AIGS / AGS core / shell nanostructures prepared by forming a shell. The TEM images show that the final shells are similar in size and have similar band edges and trap emission characteristics.
[0130] Figure 7Line graphs of AIGS / AGS core / shell nanostructures prepared by shelling with an oxygenated oleic acid Ga(III) source and an oxygen-free chlorinated Ga(III) source in oleylamine. Both nanostructures show similar emission spectra. Specific implementation plan
[0131] definition
[0132] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. The following definitions supplement the definitions in the prior art and are for current applications, and should not be transferred to any relevant or irrelevant situations, such as any jointly owned patents or applications. Although any methods and materials similar or equivalent to those described herein can be used to test the practice of the present invention, preferred materials and methods are described herein. Therefore, the terms used in the present invention are only used for the purpose of describing specific embodiments and are not intended to be limiting.
[0133] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a nanostructure" includes a plurality of such nanostructures, and the like.
[0134] The term "about" as used herein means that the value of a given number varies to ±10% of the value, for example, "about 100 nm" includes a size range from 90 nm to 110 nm (including endpoints).
[0135] "Nanostructure" is a structure with at least one size less than the region or characteristic size of about 500nm. In some embodiments, the nanostructure has a size less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm. Typically, the region or characteristic size will be along the minimum axis of the structure. The example of this structure includes nanowires, nanorods, nanotubes, branched nanostructures, nano tetrapods, tripods, bipods, nanocrystals, nanodots, quantum dots, nanoparticles, etc. Nanostructure can be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous or its combination. In some embodiments, each of the three dimensions of the nanostructure has a size less than about 500nm, less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm.
[0136] When used in relation to nanostructures, the term "heterostructure" refers to a nanostructure characterized by at least two different and / or distinguishable material types. Typically, one region of the nanostructure comprises a first material type, while a second region of the nanostructure comprises a second material type. In certain embodiments, the nanostructure comprises a core of a first material and a shell of at least one second (or third, etc.) material, wherein the different material types are distributed radially, for example, around the long axis of a nanowire, the long axis of an arm of a branched nanowire, or the center of a nanocrystal. The shell may, but need not, completely cover an adjacent material and be considered a shell or a nanostructure to be considered a heterostructure; for example, a nanocrystal characterized by a core of one material being covered by an island of a second material is a heterostructure. In other embodiments, the different material types are distributed at different locations within the nanostructure; for example, along the major axis (long axis) of a nanowire or along the long axis of an arm of a branched nanowire. Different regions within a heterostructure may comprise completely different materials, or the different regions may comprise a base material (e.g., silicon) having different dopants or different concentrations of the same dopant.
[0137] As used herein, the "diameter" of a nanostructure refers to the diameter of a cross-section perpendicular to a first axis of the nanostructure, where the first axis differs the most from the lengths of a second and third axis (the second and third axes being the two axes whose lengths are closest to being equal to each other). The first axis is not necessarily the longest axis of the nanostructure; for example, for a disc-shaped nanostructure, the cross-section will be a substantially circular cross-section perpendicular to the short longitudinal axis of the disc. If the cross-section is not circular, the diameter is the average of the major and minor axes of the cross-section. For elongated or high aspect ratio nanostructures, such as nanowires, the diameter is measured in a cross-section perpendicular to the longest axis of the nanowire. For spherical nanostructures, the diameter is measured from side to side through the center of the sphere.
[0138] When used in relation to nanostructures, the term "crystalline" or "substantially crystalline" refers to the fact that the nanostructure generally exhibits long-range order in one or more dimensions of the structure. Those skilled in the art will appreciate that the term "long-range order" will depend on the absolute size of the particular nanostructure, since the ordering of a single crystal cannot extend beyond the boundaries of the crystal. In this case, "long-range order" will mean substantially ordered at least in most dimensions of the nanostructure. In some cases, the nanostructure may be provided with an oxide or other coating, or may consist of a core and at least one shell. In this case, it is understood that the oxide, shell or other coating may, but need not, exhibit such order (e.g., it may be amorphous, polycrystalline or other). In this case, the phrase "crystalline", "substantially crystalline", "substantially single crystal" or "single crystal" refers to the central core of the nanostructure (excluding the coating or shell). The term "crystalline" or "substantially crystalline" as used herein is also intended to include structures containing various defects, stacking dislocations, atomic substitutions, etc., as long as the structure exhibits substantial long-range order (e.g., ordered over at least about 80% of the length of at least one axis of the nanostructure or its core). In addition, it should be understood that the interface between the core and the outside of the nanostructure or between the core and the adjacent shell or between the shell and the second adjacent shell may contain non-crystalline regions and may even be amorphous. This does not prevent the nanostructure from being crystalline or substantially crystalline as defined in the present invention.
[0139] When used with respect to a nanostructure, the term "single crystalline" means that the nanostructure is substantially crystalline and consists essentially of a single crystal. When used with respect to a nanostructure heterostructure comprising a core and one or more shells, "single crystalline" means that the core is substantially crystalline and consists essentially of a single crystal.
[0140] "Nanocrystal" is a substantially monocrystalline nanostructure.Therefore, nanocrystal has at least one size less than the region or characteristic size of about 500nm.In some embodiments, the nanocrystal has a size less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm.The term "nanocrystal" is intended to include a substantially monocrystalline nanostructure containing various defects, stacking dislocations, atomic substitutions, etc., and a substantially monocrystalline nanostructure without these defects, dislocations or substitutions.In the case of a nanocrystal heterostructure comprising a core and one or more shells, the core of the nanocrystal is typically substantially monocrystalline, but the shell does not need to be like this.In some embodiments, each of the three dimensions of the nanocrystal has a size less than about 500nm, less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm.
[0141] The term "quantum dot" (or "dot") refers to a nanocrystal that exhibits quantum confinement or exciton confinement. Quantum dots can be substantially homogeneous in material properties, or in certain embodiments can be heterogeneous, for example comprising a core and at least one shell. The optical properties of quantum dots can be affected by their particle size, chemical composition, and / or surface composition, and can be determined by appropriate optical tests available in the art. The ability to customize nanocrystal size (e.g., within a range of about 1 nm to about 15 nm) enables light emission coverage across the spectrum to provide great diversity in color rendering.
[0142] The term "non-oxygen containing ligand" refers to a coordinating molecule that does not contain an oxygen atom and is capable of coordinating or reacting with a metal ion as used herein.
[0143] As used in the present invention, the term "shell" refers to a material deposited on the core or previously deposited shells with the same or different composition, which is produced by a single deposition of the shell material. The exact shell thickness depends on the input and conversion of the material and precursors, and can be reported in nanometers or monolayers. As used in the present invention, "target shell thickness" refers to the expected shell thickness for calculating the required amount of precursor. As used in the present invention, "actual shell thickness" refers to the actual deposition amount of the shell material after synthesis, which can be measured by methods known in the art. For example, the actual shell thickness can be measured by comparing the particle diameter determined by the transmission electron microscope (TEM) image of the nanocrystal before and after the shell synthesis.
[0144] As used herein, the term "layer" refers to a material deposited on the core or on a previously deposited layer, resulting from a single deposition of the core or shell material. The exact layer thickness depends on the material.
[0145] A "ligand" is a molecule capable of interacting (whether weakly or strongly) with one or more faces of a nanostructure, such as through covalent, ionic, van der Waals or other molecular interactions with the nanostructure surface.
[0146] "Photoluminescence quantum yield" (QY) is the ratio of photons emitted to photons absorbed, e.g., by a nanostructure or population of nanostructures. As known in the art, quantum yield is typically determined by the absolute change in photon counts upon illumination of the sample in an integrating sphere, or by comparison methods using well-characterized standard samples with known quantum yield values.
[0147] "Peak emission wavelength" (PWL) is the wavelength where the radiation emission spectrum of a light source reaches its maximum.
[0148] As used herein, the term "full width at half maximum" (FWHM) is a measure of the quantum dot size distribution. The emission spectrum of a quantum dot typically has the shape of a Gaussian curve. The width of the Gaussian curve is defined as the FWHM and gives an idea of the particle size distribution. A smaller FWHM corresponds to a narrower quantum dot nanocrystal size distribution. The FWHM also depends on the emission wavelength maximum.
[0149] Compared to the corresponding defect emission, the band-edge emission is centered at higher energy (lower wavelength) and has a smaller shift from the absorption onset energy. In addition, the band-edge emission has a narrower wavelength distribution compared to the defect emission. Both the band-edge and defect emissions follow a normal (approximately Gaussian) wavelength distribution.
[0150] Optical density (OD) is a common method to quantify the concentration of solutes or nanoparticles. According to the Beer-Lambert law, the absorbance (also called "extinction") of a particular sample is proportional to the concentration of the solute that absorbs light of a specific wavelength.
[0151] Optical density is the attenuation of light per centimeter of material measured using a standard spectrometer, usually specified as a 1 cm path length. Nanostructured solutions are often measured by their optical density instead of mass or molarity because it is proportional to concentration and it is a more convenient way to express the amount of light absorption that occurs in a nanostructured solution at the wavelength of interest. A nanostructured solution with an OD of 100 is 100 times more concentrated (100 times more particles per mL) than a product with an OD of 1.
[0152] Optical density can be measured at any wavelength of interest, such as at a wavelength chosen to excite fluorescent nanostructures. Optical density is a measure of the intensity lost when light at a specific wavelength passes through a nanostructure solution and is calculated using the following formula:
[0153] OD = log 10 *(I OUT / I IN )
[0154] in:
[0155] I OUT = the radiation intensity entering the pool; and
[0156] I IN =Radiation intensity transmitted through the cell.
[0157] The optical density of the nanostructured solution can be measured using a UV-VIS spectrometer. Therefore, by using a UV-VIS spectrometer, the optical density can be calculated to determine the amount of quantum dots present in the sample.
[0158] Unless expressly stated otherwise, the ranges listed herein are all inclusive of the endpoint values.
[0159] Various other terms defined or otherwise described in this disclosure
[0160] AIGS Nanostructure
[0161] The present invention provides a nanostructure comprising Ag, In, Ga and S, wherein the nanostructure has a peak emission wavelength (PWL) of 480-545 nm, and wherein at least about 60% of the emission is band-edge emission.
[0162] The percentage of band edge emission is calculated by fitting Gaussian peaks (usually 2 or more) to the nanostructure emission spectrum and comparing the area of the peak closer in energy to the nanostructure band gap (which represents band edge emission) to the sum of all peak areas (band edge + defect emission).
[0163] In one embodiment, the FWHM emission spectrum of the nanostructure is less than 40nm. In another embodiment, the FWHM of the nanostructure is 36-38nm. In another embodiment, the QY of the nanostructure is at least 58%. In another embodiment, the QY of the nanostructure is 58-65%. In another embodiment, the QY of the nanostructure is about 65%. In some embodiments, at least 80% of the emission is band edge emission. In other embodiments, at least 90% of the emission is band edge emission. In other embodiments, at least 95% of the emission is band edge emission. In some embodiments, 92-98% of the emission is band edge emission. In some embodiments, 93-96% of the emission is band edge emission. In another embodiment, the nanostructure is a quantum dot.
[0164] The AIGS nanostructures provide high blue light absorption. As a prediction of blue light absorption efficiency, the optical density (OD) at 450 nm per mass was calculated. 450 The optical density (OD) of the nanostructure solution in a 1 cm path length cuvette is then divided by the dry mass per mL (mg / mL) of the same solution after all volatiles have been removed under vacuum (<200 mTorr). In one embodiment, the OD of the nanostructure provided by the present invention is 450 / Mass (mL mg -1 cm -1 ) is at least 0.8. In another embodiment, the OD of the nanostructure 450 / Mass (mL mg -1 cm -1 ) is 0.8-2.5. In another embodiment, the OD of the nanostructure 450 / Mass (mL mg -1 cm -1 ) is 0.87-1.9.
[0165] In one embodiment, the nanostructure is a core-shell nanostructure. In another embodiment, the nanostructure has Ag, In, Ga, and S in the core and Ga and S in the shell (AIGS / GS). In another embodiment, the nanostructure has Ag, In, Ga, and S in the core and Ag, Ga, and S in the shell (AIGS / AGS).
[0166] In one embodiment, the nanostructures have an average diameter of less than 10 nm as measured by TEM. In another embodiment, the average diameter is about 5 nm.
[0167] AIGS nanostructures prepared using GaX3 (X = F, Cl or Br) precursors and oxygen-free ligands
[0168] Reports on AIGS preparation in the literature do not attempt to exclude oxygen-containing ligands. In AIGS coatings with gallium-containing shells, oxygen-containing ligands are generally used to stabilize the Ga precursor. Gallium acetylacetonate (III) is generally used as a precursor that is easy to handle in air, while gallium chloride (III) needs to be handled carefully due to humidity sensitivity. For example, in Kameyama et al. ACS Appl. Mater. Interfaces 10: 42844-42855 (2018), gallium acetylacetonate (III) is used as a precursor for core and core / shell structures. Because gallium has a high affinity for oxygen, when Ga and S precursors are used to prepare shells containing significant gallium content, oxygen-containing ligands and the use of gallium precursors that are not prepared under oxygen-free conditions may produce unwanted side reactions, such as gallium oxidation. These side reactions may cause defects in the shell and lead to lower quantum yields.
[0169] In some embodiments, an AIGS nanostructure is prepared using oxygen-free GaX3 (X=F, Cl or Br) as a precursor for preparing an AIGS core. In some embodiments, in preparing at least one shell on the AIGS nanostructure, GaX3 (X=F, Cl or Br) is used as a precursor and oxygen-free ligands are used to prepare the AIGS nanostructure. In some embodiments, in preparing an AIGS core and in preparing at least one shell on the AIGS core, GaX3 (X=F, Cl or Br) is used as a precursor and oxygen-free ligands are used to prepare the AIGS nanostructure. In some embodiments, in preparing an AIGS core and in preparing a shell on the AIGS core, GaX3 (X=F, Cl or Br) is used as a precursor and oxygen-free ligands are used to prepare the AIGS nanostructure.
[0170] The present invention provides a nanostructure comprising Ag, In, Ga and S, wherein the peak emission wavelength (PWL) of the nanostructure is 480-545 nm, and wherein the nanostructure is prepared using a GaX3 (X=F, Cl or Br) precursor and an oxygen-free ligand.
[0171] In some embodiments, nanostructures prepared using GaX3 (X = F, Cl or Br) precursors and oxygen-free ligands exhibit a FWHM emission spectrum of 35 nm or less. In some embodiments, nanostructures prepared using GaX3 (X = F, Cl or Br) precursors and oxygen-free ligands exhibit a FWHM of 30-38 nm. In some embodiments, nanostructures prepared using GaX3 (X = F, Cl or Br) precursors and oxygen-free ligands have a QY of at least 75%. In some embodiments, nanostructures prepared using GaX3 (X = F, Cl or Br) precursors and oxygen-free ligands have a QY of 75-90%. In some embodiments, nanostructures prepared using GaX3 (X = F, Cl or Br) precursors and oxygen-free ligands have a QY of about 80%. In some embodiments, the nanostructures are quantum dots.
[0172] The AIGS nanostructures prepared in the present invention provide high blue light absorption. In some embodiments, the nanostructures have an OD of at least 0.8. 450 / Mass (mL·mg -1 cm -1 In some embodiments, the nanostructures have an OD of 0.8-2.5. 450 / Mass (mL mg -1 cm -1 In another embodiment, the nanostructures have an OD of 0.87-1.9. 450 / Mass (mL mg -1 cm -1 ).
[0173] In some embodiments, the nanostructure is a core / shell nanostructure. In some embodiments, the nanostructure comprises Ag, In, Ga, and S in the core and Ga and S in the shell. In some embodiments, the nanostructure is an AIGS / AGS core / shell nanostructure prepared using a GaX3 (X=F, Cl, or Br) precursor and oxygen-free ligands in the core. In some embodiments, the nanostructure is an AIGS / AGS core / shell nanostructure prepared using a GaX3 (X=F, Cl, or Br) precursor and oxygen-free ligands in the shell. In some embodiments, the nanostructure is an AIGS / AGS core / shell nanostructure prepared using a GaX3 (X=F, Cl, or Br) precursor and oxygen-free ligands in the core and shell. In some embodiments, the AIGS / AGS core / shell nanostructure is prepared by reacting a preformed In-Ga reagent with an Ag2S nanostructure to obtain an AIGS nanostructure, followed by reacting with an oxygen-free Ga salt to form an AIGS / AGS core-shell nanostructure.
[0174] Method for preparing AIGS nanostructure
[0175] The present invention provides a method for preparing a core / shell nanostructure having a PWL of 480-545 nm, wherein at least about 60% of the emission is band edge emission, the method comprising:
[0176] (a) preparing a mixture comprising Ag-In-Ga-S (AIGS) cores, a sulfur source and a ligand;
[0177] (b) adding the mixture obtained in (a) to a mixture of gallium carboxylate and ligand at a temperature of 180-300° C. to obtain a nanostructure having a PWL of 480-545 nm, wherein at least about 60% of the emission is band edge emission; and
[0178] (c) separating the nanostructures.
[0179] The present invention also provides a method for preparing an AIGS / AGS core-shell nanostructure, which comprises:
[0180] reacting Ga(acetylacetonate)3, InCl3 and a ligand, optionally in a solvent, at a temperature sufficient to obtain an In-Ga reagent, and
[0181] reacting the In-Ga reagent with the Ag2S nanostructure at a temperature sufficient to produce the AIGS nanostructure,
[0182] The AIGS nanostructures are reacted with an oxygen-free Ga salt in a solvent containing a ligand at a temperature sufficient to form AIGS / AGS core-shell nanocrystals.
[0183] In some embodiments, the ligand is an alkylamine. In some embodiments, the alkylamine ligand is oleylamine. In some embodiments, the ligand is used in excess and acts as a solvent, and the solvent is not present in the reaction. In some embodiments, the solvent is present in the reaction. In some embodiments, the solvent is a high boiling point solvent. In some embodiments, the solvent is octadecene, squalane, dibenzyl ether or xylene. In some embodiments, the sufficient temperature in (a) is 100-280°C; the sufficient temperature in (b) is 150-260°C; and the sufficient temperature in (c) is 170-280°C. In some embodiments, the sufficient temperature in (a) is about 210°C, the sufficient temperature in (b) is about 210°C, and the sufficient temperature in (c) is about 240°C.
[0184] In some embodiments, at least 80% of the emission is band edge emission. In other embodiments, at least 90% of the emission is band edge emission. In other embodiments, at least 95% of the emission is band edge emission. In some embodiments, 92-98% of the emission is band edge emission. In some embodiments, 93-96% of the emission is band edge emission. In another embodiment, the nanostructure is a quantum dot.
[0185] Examples of ligands are disclosed in U.S. Pat. Nos. 7,572,395, 8,143,703, 8,425,803, 8,563,133, 8,916,064, 9,005,480, 9,139,770, and 9,169,435 and U.S. Patent Application Publication No. 2008 / 0118755. In one embodiment, the ligand is an alkylamine. In some embodiments, the ligand is an alkylamine selected from dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine.
[0186] In some embodiments, the sulfur source in (a) includes trioctylphosphine sulfide, elemental sulfur, octyl mercaptan, dodecanethiol, octadecyl mercaptan, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluene mercaptan, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl) sulfide, trioctylphosphine sulfide or a combination thereof. In some embodiments, the sulfur source in (a) is derived from S8.
[0187] In one embodiment, the sulfur source is derived from S8.
[0188] In one embodiment, the temperature in (a) and (b) is about 270°C.
[0189] In some embodiments, the mixture in (b) further comprises a solvent. In some embodiments, the solvent is trioctylphosphine, dibenzyl ether or squalane.
[0190] In some embodiments, the gallium carboxylate is C 2-24 Gallium carboxylate. 2-24 Examples of carboxylates include acetate, propionate, butyrate, valerate, hexanoate, heptanoate, octanoate, nonanoate, decanoate, undecanoate, tridecanoate, tetradecanoate, pentadecanoate, hexadecanoate, octadecanoate (oleate), nonadecanoate and eicosanoate. In one embodiment, the gallium carboxylate is gallium oleate.
[0191] In some embodiments, the ratio of gallium carboxylate to AIGS core is 0.008-0.2 mmol gallium carboxylate / mg AIGS. In one embodiment, the ratio of gallium carboxylate to AIGS core is about 0.04 mmol gallium carboxylate / mg AIGS.
[0192] In another embodiment, the AIGS / AGS core / shell nanostructures are separated, for example, by precipitation. In some embodiments, the AIGS / AGS core / shell nanostructures are precipitated by adding a non-solvent for the AIGS / AGS core / shell nanostructures. In some embodiments, the non-solvent is a toluene / ethanol mixture. The precipitated nanostructures can be further separated by centrifugation and washing with a non-solvent for the nanostructures.
[0193] The present invention also provides a method for preparing a nanostructure having a PWL of 480-545 nm, and wherein at least about 60% of the emission is band edge emission; the method comprising:
[0194] (a) preparing a mixture comprising AIGS cores and gallium halide in a solvent and maintaining the mixture for a time sufficient to obtain AIGS nanostructures having a PWL of 480-545 nm, wherein at least about 60% of the emission is band edge emission; and
[0195] (b) separating the nanostructures.
[0196] In some embodiments, at least 80% of the emission is band edge emission. In other embodiments, at least 90% of the emission is band edge emission. In other embodiments, at least 95% of the emission is band edge emission. In another embodiment, the nanostructure is a quantum dot.
[0197] In some embodiments, the gallium halide is gallium chloride, gallium bromide, or gallium iodide. In one embodiment, the gallium halide is gallium iodide.
[0198] In some embodiments, the solvent comprises trioctylphosphine.In some embodiments, the solvent comprises toluene.
[0199] In some embodiments, the sufficient time in (a) is 0.1-200 hours. In some embodiments, the sufficient time in (a) is about 20 hours.
[0200] In some embodiments, the mixture is maintained at 20-100° C. In one embodiment, the mixture is maintained at about room temperature (20° C.-25° C.).
[0201] In some embodiments, the molar ratio of gallium halide to AIGS core is from about 0.1 to about 30.
[0202] In another embodiment, the AIGS nanostructures are separated, for example, by precipitation. In some embodiments, the AIGS nanostructures are precipitated by adding a non-solvent for the AIGS nanostructures. In some embodiments, the non-solvent is a toluene / ethanol mixture. The precipitated nanostructures can be further separated by centrifugation and / or washing with a non-solvent for the nanostructures.
[0203] Preparation method of AIGS nanostructures using GaX3 (X=F, Cl or Br) precursor and oxygen-free ligands
[0204] The present invention provides a method for preparing a core / shell nanostructure having a PWL of 480-545 nm, wherein at least about 60% of the emission is band edge emission, the method comprising:
[0205] (a) preparing a mixture comprising Ag-In-Ga-S (AIGS) cores, a sulfur source and a ligand;
[0206] (b) adding the mixture obtained in (a) to a mixture of GaX3 (X = F, Cl or Br) and an oxygen-free ligand at a temperature of 180-300°C to obtain a nanostructure having a PWL of 480-545 nm, wherein at least about 60% of the emission is band edge emission; and
[0207] (d) separating the nanostructures.
[0208] In some embodiments, the preparation in (a) is performed under oxygen-free conditions. In some embodiments, the preparation in (a) is performed in a glove box.
[0209] In some embodiments, the adding in (b) is performed under oxygen-free conditions. In some embodiments, the adding in (b) is performed in a glove box.
[0210] In some embodiments, at least 80% of the emission is band edge emission. In other embodiments, at least 90% of the emission is band edge emission. In other embodiments, at least 95% of the emission is band edge emission. In another embodiment, the nanostructure is a quantum dot.
[0211] Examples of ligands are disclosed in U.S. Patent Nos. 7,572,395, 8,143,703, 8,425,803, 8,563,133, 8,916,064, 9,005,480, 9,139,770, and 9,169,435 and U.S. Patent Application Publication No. 2008 / 0118755. In some embodiments, the ligand in (a) is an oxygen-free ligand. In some embodiments, the ligand in (b) is an oxygen-free ligand. In some embodiments, the ligand in (a) and (b) is an alkylamine. In some embodiments, the ligand is an alkylamine selected from dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine. In some embodiments, the ligand in (a) is oleylamine. In some embodiments, the ligand in (b) is oleylamine. In some embodiments, the ligand in (a) and (b) is oleylamine.
[0212] In one embodiment, the sulfur source is derived from S8.
[0213] In one embodiment, the temperature in (a) and (b) is about 270°C.
[0214] In some embodiments, the mixture in (b) further comprises a solvent. In some embodiments, the solvent is trioctylphosphine, dibenzyl ether or squalane.
[0215] In some embodiments, GaX3 is gallium chloride, gallium fluoride, or gallium iodide. In some embodiments, GaX3 is gallium chloride. In some embodiments, GaX3 is Ga(III) chloride.
[0216] In some embodiments, the ratio of GaX3 to AIGS core is 0.008-0.2 mmol GaX3 / mg AIGS. In some embodiments, the molar ratio of GaX3 to AIGS core is about 0.1 to about 30. In some embodiments, the ratio of GaX3 to AIGS core is about 0.04 mmol GaX3 / mg AIGS.
[0217] In some embodiments, the AIGS / AGS core / shell nanostructures are separated, for example, by precipitation. In some embodiments, the AIGS / AGS core / shell nanostructures are precipitated by adding a non-solvent for the AIGS / AGS core / shell nanostructures. In some embodiments, the non-solvent is a toluene / ethanol mixture. The precipitated nanostructures can be further separated by centrifugation and / or washing with a non-solvent for the nanostructures.
[0218] In some embodiments, the mixture in (a) is maintained at 20° C.-100° C. In some embodiments, the mixture in (a) is maintained at about room temperature (20° C. 0-25° C.).
[0219] In some embodiments, the mixture in (b) is maintained at 200°C-300°C for 0.1 hour to 200 hours. In some embodiments, the mixture in (b) is maintained at 200°C-300°C for about 20 hours.
[0220] AIGS core
[0221] The synthesis of Group III-V nanostructures has been described in U.S. Patent Nos. 5,505,928, 6,306,736, 6,576,291, 6,788,453, 6,821,337, 7,138,098, 7,557,028, 8,062,967, 7,645,397, and 8,282,412 and U.S. Patent Application Publication No. 2015 / 236195. The synthesis of Group III-V nanostructures is also described in Wells, RL et al. “The use of tris(trimethylsilyl)arsine to prepare gallium arsenide and indiumarsenide,” Chem. Mater. 1:4-6 (1989) and Guzelian, AA et al. “Colloidal chemical synthesis and characterization of InAs nanocrystal quantum dots,” Appl. Phys. Lett. 69:1432-1434 (1996).
[0222] In some embodiments, the core is doped. In some embodiments, the dopant of the nanocrystal core comprises a metal, including one or more transition metals. In some embodiments, the dopant is a transition metal selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au and combinations thereof. In some embodiments, the dopant is ZnS, ZnSe, ZnTe, CdSe, CdS, CdTe, HgS, HgSe, HgTe, CuInS2, CuInSe2, AlN, AlP, AlAs, GaN, GaP or GaAs.
[0223] In some embodiments, the core is purified prior to shell deposition. In some embodiments, the core is filtered to remove precipitate from the core solution.
[0224] Nanostructured shell
[0225] In some embodiments, the shell comprises a mixture of silver, gallium, and sulfur elements deposited on the core or core / shell structure.
[0226] In some embodiments, the shell is doped. In some embodiments, the dopant of the nanocrystal shell comprises a metal, which includes one or more transition metals. In some embodiments, the dopant is a transition metal selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au and combinations thereof. In some embodiments, the dopant is ZnS, ZnSe, ZnTe, CdSe, CdS, CdTe, HgS, HgSe, HgTe, CuInS2, CuInSe2, AlN, AlP, AlAs, GaN, GaP or GaAs.
[0227] In some embodiments, the core / shell nanostructures are purified prior to depositing additional shells. In some embodiments, the core / shell nanostructures are filtered to remove precipitates from the core / shell nanostructure solution.
[0228] Nanostructured compositions
[0229] In some embodiments, the present disclosure provides a nanostructure composition comprising:
[0230] (a) at least one population of nanostructures, wherein the nanostructures have a core comprising Ag, In, Ga, and S (AIGS) and a shell comprising Ag, Ga, and S (AGS), have a PWL of 480-545 nm, and wherein at least about 80% of the emission is band-edge emission; and
[0231] (b) at least one organic resin.
[0232] In some embodiments, at least 80% of the emission is band edge emission. In other embodiments, at least 90% of the emission is band edge emission. In other embodiments, at least 95% of the emission is band edge emission. In some embodiments, 92-98% of the emission is band edge emission. In some embodiments, 93-96% of the emission is band edge emission. In another embodiment, the nanostructure is a quantum dot.
[0233] In some embodiments, the nanostructure composition further comprises at least one second nanostructure population. The nanostructure with a PWL of 480-545nm emits green light. Additional nanostructure populations that emit in the green, yellow, orange and / or red regions of the spectrum can be added. These nanostructures have a PWL greater than 545nm. In some embodiments, the PWL of the nanostructure is 550-750nm. The size of the nanostructure determines the emission wavelength. The at least one second nanostructure population can include III-V group nanocrystals selected from BN, BP, BAs, BSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs and InSb. In some embodiments, the core of the second nanostructure population is an InP nanocrystal.
[0234] Organic resin
[0235] In some embodiments, the organic resin is a thermosetting resin or an ultraviolet (UV) curable resin. In some embodiments, the organic resin is cured by a basketball roll-to-roll process.
[0236] Thermosetting resins require a cure in which they undergo an irreversible molecular crosslinking process that renders the resin infusible. In some embodiments, the thermosetting resin is an epoxy resin, a phenolic resin, a vinyl resin, a melamine resin, a urea resin, an unsaturated polyester resin, a polyurethane resin, an allyl resin, an acrylic resin, a polyamide resin, a polyamide-imide resin, a phenolamine polycondensation resin, a urea-melamine polycondensation resin, or a combination thereof.
[0237] In some embodiments, the thermosetting resin is an epoxy resin. Epoxy resins are easily cured without releasing volatiles or byproducts from various chemicals. Epoxy resins are also compatible with most substrates and easily wet the surface. See Boyle, MA, et al., "Epoxy Resins," Composites, Vol. 21, ASM Handbook, pp. 78-89 (2001).
[0238] In some embodiments, the organic resin is a silicone thermoset resin. In some embodiments, the silicone thermoset resin is OE6630A or OE6630B (Dow Corning Corporation, Auburn, MI).
[0239] In some embodiments, a thermal initiator is used. In some embodiments, the thermal initiator is AIBN [2,2'-azobis(2-methylpropionitrile)] or benzoyl peroxide.
[0240] UV curing resin is a polymer that solidifies and hardens quickly when exposed to a specific light wavelength. In some embodiments, UV curing resin is a resin with a free radical polymerization group (such as (meth) acryloxy, vinyloxy, styryl or vinyl) and a cationic polymerizable group (such as epoxy, thioepoxy, vinyloxy or oxetane) as a functional group. In some embodiments, UV curing resin is a polyester resin, a polyether resin, a (meth) acrylic resin, an epoxy resin, a polyurethane resin, an alkyd resin, a spiroacetal resin, a polybutadiene resin or a polythiol polyene resin.
[0241] In some embodiments, the UV curable resin is selected from polyurethane acrylate, allyloxylated cyclohexyl diacrylate, bis(acryloxyethyl) hydroxyisocyanurate, bis(acryloxyneopentyl glycol) adipate, bisphenol A diacrylate, bisphenol A dimethacrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, 1,3-butanediol diacrylate, 1,3-butanediol dimethacrylate, dicyclopentanyl diacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, dipentaerythritol hexaacrylate, dipentaerythritol monohydroxypentaacrylate, di(trimethylolpropane) tetraacrylate, ethylene glycol dimethacrylate, glyceryl methacrylate, 1,6-hexanediol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol hydroxypivalate diacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, Phosphoric acid dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, tetraethylene glycol diacrylate, tetrabromobisphenol A diacrylate, triethylene glycol divinyl ether, triglycerol diacrylate, trimethylolpropane triacrylate, tripropylene glycol diacrylate, tri(acryloxyethyl) isocyanurate, phosphoric acid triacrylate, phosphoric acid diacrylate, propargyl acrylate, vinyl terminated polydimethylsiloxane, vinyl terminated diphenylsiloxane-dimethylsiloxane copolymer, vinyl terminated polyphenylmethylsiloxane, vinyl terminated trifluoromethylsiloxane-dimethylsiloxane copolymer, vinyl terminated diethylsiloxane-dimethylsiloxane copolymer, vinyl methylsiloxane, monomethacryloxypropyl terminated polydimethylsiloxane, monovinyl terminated polydimethylsiloxane, monoallyl-monotrimethylsiloxy terminated polyethylene oxide, and combinations thereof.
[0242] In some embodiments, the UV curable resin is a thiol functional compound, which can be crosslinked with isocyanates, epoxides or unsaturated compounds under UV curing conditions. In some embodiments, the polythiol is pentaerythritol tetrakis (3-mercapto-propionic acid) (PETMP); trimethylol-propane tris (3-mercaptopropionic acid) (TMPMP); diol di (3-mercaptopropionic acid) (GDMP); tris [25- (3-mercapto-propionyloxy) ethyl] isocyanurate (TEMPIC); dipentaerythritol hexa (3-mercaptopropionic acid) (Di-PETMP); ethoxylated trimethylolpropane tris (3-mercaptopropionic acid) (ETTMP 1300 and ETTMP 700); polycaprolactone tetrakis (3-mercaptopropionic acid) (PCL4MP1350); pentaerythritol tetrakis mercaptoacetate (PETMA); trimethylolpropane tris mercaptoacetate (TMPMA); or diol dimercaptoacetate (GDMA). These compounds are marketed by Bruno Bock, Marschacht, Germany under the trade name Sale.
[0243] In some embodiments, the UV curable resin is a polythiol. In some embodiments, the UV curable resin is a polythiol selected from ethylene glycol bis(thioglycolate), ethylene glycol bis(3-mercaptopropionate), trimethylolpropane tris(thioglycolate), trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(thioglycolate), pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) and combinations thereof. In some embodiments, the UV curable resin is PETMP.
[0244] In some embodiments, the UV curable resin is a thiol-ene formulation comprising polythiol and 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (TTT). In some embodiments, the UV curable resin is a thiol-ene formulation comprising PETMP and TTT.
[0245] In some embodiments, the UV curable resin further comprises a photoinitiator. The photoinitiator initiates a crosslinking and / or curing reaction of the photosensitive material during exposure to light. In some embodiments, the photoinitiator is acetophenone-based, benzoin-based or thioxanthone-based.
[0246] In some embodiments, the photoinitiator is a vinyl acrylate based resin. In some embodiments, the photoinitiator is MINS-311RM (Minuta Technology Co., Ltd, Korea).
[0247] In some embodiments, the photoinitiator is 127. 184. 184D, 2022, 2100, 250, 270, 2959, 369, 369EG, 379, 500, 651, 754, 784, 819, 819Dw, 907, 907FF, Oxe01, TPO-L, 1173, 1173D, 4265, BP or MBF (BASF Corporation, Wyandotte, MI). In some embodiments, the photoinitiator is TPO (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide) or MBF (methyl benzoylformate).
[0248] In some embodiments, the weight percentage of the at least one organic resin in the nanostructure composition is about 5% to about 99%, about 5% to about 95%, about 5% to about 90%, about 5% to about 80%, about 5% to about 70%, about 5% to about 60%, about 5% to about 50%, about 5% to about 40%, about 5% to about 30%, about 5% to about 20%, about 5% to about 10%, about 10% to about 99%, about 10% to about 95%. about 10% to about 90%, about 10% to about 80%, about 10% to about 70%, about 10% to about 60%, about 10% to about 50%, about 10% to about 40%, about 10% to about 30%, about 10% to about 20%, about 20% to about 99%, about 20% to about 95%, about 20% to about 90%, about 20% to about 80%, about 20% to about 70%, about 2 0% to about 60%, about 20% to about 50%, about 20% to about 40%, about 20% to about 30%, about 30% to about 99%, about 30% to about 95%, about 30% to about 90%, about 30% to about 80%, about 30% to about 70%, about 30% to about 60%, about 30% to about 50%, about 30% to about 40%, about 40% to about 99%, about 40% to about about 95%, about 40% to about 90%, about 40% to about 80%, about 40% to about 70%, about 40% to about 60%, about 40% to about 50%, about 50% to about 99%, about 50% to about 95%, about 50% to about 90%, about 50% to about 80%, about 50% to about 70%, about 50% to about 60%, about 60% to about 99%, about 60% to about 95%. 5%, about 60% to about 90%, about 60% to about 80%, about 60% to about 70%, about 70% to about 99%, about 70% to about 95%, about 70% to about 90%, about 70% to about 80%, about 80% to about 99%, about 80% to about 95%, about 80% to about 90%, about 90% to about 99%, about 80% to about 95%, about 80% to about 90%, about 90% to about 99%, about 90% to about 95%, or about 95% to about 99%.
[0249] Method for preparing AIGS nanostructured composition
[0250] The present disclosure provides a method for preparing a nanostructure composition, the method comprising:
[0251] (a) providing at least one population of AIGS / AGS core-shell nanostructures comprising Ag, In, Ga, and S, wherein the nanostructures have a PWL of 480-545 nm, and wherein at least about 80% of the emission is band-edge emission; and
[0252] (b) mixing at least one organic resin with the composition of (a).
[0253] In some embodiments, at least 80% of the emission is band edge emission. In other embodiments, at least 90% of the emission is band edge emission. In other embodiments, at least 95% of the emission is band edge emission. In some embodiments, 92-98% of the emission is band edge emission. In some embodiments, 93-96% of the emission is band edge emission. In another embodiment, the nanostructure is a quantum dot.
[0254] The present disclosure also provides a method for preparing a nanostructure composition, the method comprising:
[0255] (a) providing at least one population of nanostructures comprising Ag, In, Ga, and S, wherein the nanostructures have a PWL of 480-545 nm, wherein at least about 60% of the emission is band edge emission, and wherein the nanostructures are prepared using a GaX3 (X=F, Cl, or Br) precursor and a non-oxygen containing ligand; and
[0256] (b) mixing at least one organic resin with the composition of (a).
[0257] The present disclosure also provides a method for preparing a nanostructure composition, the method comprising:
[0258] (a) providing at least one population of AIGS / AGS core-shell nanostructures, wherein the nanostructures have a PWL of 480-545 nm, wherein at least about 80% of the emission is band-edge emission, and wherein the nanostructures exhibit a QY of 80-99%; and
[0259] (b) mixing at least one organic resin with the composition of (a).
[0260] In some embodiments, at least one population of nanostructures is mixed with at least one organic resin at a stirring rate of about 100 rpm to about 10,000 rpm, about 100 rpm to about 5,000 rpm, about 100 rpm to about 3,000 rpm, about 100 rpm to about 1,000 rpm, about 100 rpm to about 500 rpm, about 500 rpm to about 10,000 rpm, about 500 rpm to about 5,000 rpm, about 500 rpm to about 3,000 rpm, about 500 rpm to about 1,000 rpm, about 1,000 rpm to about 10,000 rpm, about 1,000 rpm to about 5,000 rpm, about 1,000 rpm to about 3,000 rpm, about 3,000 rpm to about 10,000 rpm, about 3,000 rpm to about 10,000 rpm, or about 5,000 rpm to about 10,000 rpm.
[0261] In some embodiments, at least one population of nanostructures is mixed with at least one organic resin for about 10 minutes to about 24 hours, about 10 minutes to about 20 hours, about 10 minutes to about 15 hours, about 10 minutes to about 10 hours, about 10 minutes to about 5 hours, about 10 minutes to about 1 hour, about 10 minutes to about 30 minutes, about 30 minutes to about 24 hours, about 30 minutes to about 20 hours, about 30 minutes to about 15 hours, about 30 minutes to about 10 hours, about 30 minutes to about 5 hours, about 30 minutes to about 1 hour, about 10 minutes to about 30 minutes, about 30 minutes to about 24 hours, about 30 minutes to about 20 hours, about 30 minutes to about 15 hours, about 30 minutes to about 10 hours, about 30 minutes to about 5 hours, about 30 minutes to about A time of about 1 hour, about 1 hour to about 24 hours, about 1 hour to about 20 hours, about 1 hour to about 15 hours, about 1 hour to about 10 hours, about 1 hour to about 5 hours, about 5 hours to about 24 hours, about 5 hours to about 20 hours, about 5 hours to about 15 hours, about 5 hours to about 10 hours, about 10 hours to about 24 hours, about 10 hours to about 20 hours, about 10 hours to about 15 hours, about 15 hours to about 24 hours, about 15 hours to about 20 hours, or about 20 hours to about 24 hours.
[0262] In some embodiments, at least one population of nanostructures is mixed with at least one organic resin at a temperature of about -5°C to about 100°C, about -5°C to about 75°C, about -5°C to about 50°C, about -5°C to about 23°C, about 23°C to about 100°C, about 23°C to about 75°C, about 23°C to about 50°C, about 50°C to about 100°C, about 50°C to about 75°C, or about 75°C to about 100°C. In some embodiments, at least one organic resin is mixed with at least one population of nanostructures at a temperature of about 23°C to about 50°C.
[0263] In some embodiments, if more than one organic resin is used, the organic resins are added and mixed together. In some embodiments, the first organic resin is mixed with the second organic resin at a stirring rate of about 100 rpm to about 10,000 rpm, about 100 rpm to about 5,000 rpm, about 100 rpm to about 3,000 rpm, about 100 rpm to about 1,000 rpm, about 100 rpm to about 500 rpm, about 500 rpm to about 10,000 rpm, about 500 rpm to about 5,000 rpm, about 500 rpm to about 3,000 rpm, about 500 rpm to about 1,000 rpm, 1,000 rpm to about 10,000 rpm, about 1,000 rpm to about 5,000 rpm, about 1,000 rpm to about 3,000 rpm, about 3,000 rpm to about 10,000 rpm, about 3,000 rpm to about 10,000 rpm, or about 5,000 rpm to about 10,000 rpm.
[0264] In some embodiments, the first organic resin is mixed with the second organic resin for about 10 minutes to about 24 hours, about 10 minutes to about 20 hours, about 10 minutes to about 15 hours, about 10 minutes to about 10 hours, about 10 minutes to about 5 hours, about 10 minutes to about 1 hour, about 10 minutes to about 30 minutes, about 30 minutes to about 24 hours, about 30 minutes to about 20 hours, about 30 minutes to about 15 hours, about 30 minutes to about 10 hours, about 30 minutes to about 5 hours, about 30 minutes to about 1 hour, The invention relates to a time period of about 1 hour to about 24 hours, about 1 hour to about 20 hours, about 1 hour to about 15 hours, about 1 hour to about 10 hours, about 1 hour to about 5 hours, about 5 hours to about 24 hours, about 5 hours to about 20 hours, about 5 hours to about 15 hours, about 5 hours to about 10 hours, about 10 hours to about 24 hours, about 10 hours to about 20 hours, about 10 hours to about 15 hours, about 15 hours to about 24 hours, about 15 hours to about 20 hours, or about 20 hours to about 24 hours.
[0265] Characteristics of AIGS nanostructures
[0266] In some embodiments, the nanostructure is a core / shell nanostructure. In some embodiments, the nanostructure is an AIGS / AGS core-shell nanostructure.
[0267] In some embodiments, the nanostructures exhibit a high photoluminescence quantum yield. In some embodiments, the nanostructures exhibit a high photoluminescence quantum yield of about 50% to about 99%, about 50% to about 95%, about 50% to about 90%, about 50% to about 85%, about 50% to about 80%, about 50% to about 70%, about 50% to about 60%, about 60% to about 99%, about 60% to about 95%, about 60% to about 90%, about 60% to about 85%, about 60% to about 80%, about 60% to about 70%, about 70% to about 99%, about 70% to about 99%. In some embodiments, the nanostructures exhibit a photoluminescence quantum yield of about 82% to about 96%, about 85% to about 96%, and about 93% to about 94%.
[0268] The photoluminescence spectrum of the nanostructures can cover substantially any desired portion of the spectrum. In some embodiments, the emission maximum of the photoluminescence spectrum of the nanostructures is between 300nm-750nm, 300nm-650nm, 300nm-550nm, 300nm-450nm, 450nm-750nm, 450nm-650nm, 450nm-550nm, 450nm-750nm, 450nm-650nm, 450nm-550nm, 550nm-750nm, 550nm-650nm, or 650nm-750nm. In some embodiments, the emission maximum of the photoluminescence spectrum of the nanostructures is between 450nm and 550nm.
[0269] The size distribution of the nanostructures can be relatively narrow. In some embodiments, the full width at half maximum of the photoluminescence spectrum of the nanostructure population can be 10nm-60nm, 10nm-40nm, 10nm-30nm, 10nm-20nm, 20nm-60nm, 20nm-40nm, 20nm-30nm, 30nm-60nm, 30nm-40nm or 40nm-60nm. In some embodiments, the full width at half maximum of the photoluminescence spectrum of the nanostructure population can be 35nm-50nm.
[0270] In some embodiments, the nanostructure emits light with a peak emission wavelength (PWL) of about 400nm to about 650nm, about 400nm to about 600nm, about 400nm to about 550nm, about 400nm to about 500nm, about 400nm to about 450nm, about 450nm to about 650nm, about 450nm to about 600nm, about 450nm to about 550nm, about 450nm to about 500nm, about 500nm to about 650nm, about 500nm to about 600nm, about 500nm to about 550nm, about 550nm to about 650nm, about 550nm to about 600nm, or about 600nm to about 650nm. In some embodiments, the nanostructure emits light with a PWL of about 500nm to about 550nm.
[0271] As a prediction of blue light absorption efficiency, the optical density (OD) at 450 nm per mass was used. 450 The optical density (OD) of the nanostructures at 450 nm can be calculated by measuring the optical density of a solution of the nanostructures in a 1 cm path length cuvette and then dividing by the dry mass (mg / mL) of the same solution after all volatiles have been removed under vacuum (<200 mTorr). In some embodiments, the nanostructures are present at an optical density (OD) of 450 nm per mass. 450 / mass) is about 0.28 / mg to about 0.5 / mg, about 0.28 / mg to about 0.4 / mg, about 0.28 / mg to about 0.35 / mg, about 0.28 / mg to about 0.32 / mg, about 0.32 / mg to about 0.5 / mg, about 0.32 / mg to about 0.4 / mg, about 0.32 / mg to about 0.35 / mg, about 0.35 / mg to about 0.5 / mg, about 0.35 / mg to about 0.4 / mg, or about 0.4 / mg to about 0.5 / mg.
[0272] membrane
[0273] Nanostructures of the present invention can be embedded in polymer matrix using any suitable method. As used in the present invention, the term "embedded" is used to represent that the nanostructure is surrounded or wrapped by the polymer that constitutes the major component of the matrix. In some embodiments, at least one nanostructure colony is suitably evenly distributed in the whole matrix. In some embodiments, at least one nanostructure colony is distributed according to application-specific distribution. In some embodiments, the nanostructure is mixed in a polymer and applied to the surface of a substrate.
[0274] In some embodiments, the present disclosure provides a nanostructured film layer comprising:
[0275] (a) at least one population of nanostructures comprising AIGS / AGS core-shell nanostructures, wherein the nanostructures have a PWL of 480-545, wherein at least about 80% of the emission is band-edge emission, and wherein the nanostructures exhibit a QY of 80-99.9%; and
[0276] (b) at least one organic resin.
[0277] The present disclosure also provides a method for preparing a nanostructured film layer, the method comprising:
[0278] (a) providing at least one population of AIGS / AGS core-shell nanostructures, wherein the nanostructures have a PWL of 480-545 nm, wherein at least about 80% of the emission is band-edge emission, and wherein the nanostructures exhibit a QY of 80-99.9%; and
[0279] (b) mixing at least one organic resin with the composition of (a).
[0280] In some embodiments, at least 80% of the emission is band edge emission. In other embodiments, at least 90% of the emission is band edge emission. In other embodiments, at least 95% of the emission is band edge emission. In some embodiments, 92-98% of the emission is band edge emission. In some embodiments, 93-96% of the emission is band edge emission. In another embodiment, the nanostructure is a quantum dot.
[0281] In some embodiments, the nanostructured film layer is a color conversion layer.
[0282] The nanostructure composition can be deposited by any suitable method known in the art, including but not limited to painting, spraying, solvent spraying, wet coating, adhesive coating, spin coating, tape coating, roller coating, flow coating, inkjet spraying, drop casting, scraping, mist deposition or a combination thereof. Preferably, the quantum dot composition is cured after deposition. Suitable curing methods include photocuring, such as UV curing, and thermal curing. Conventional laminating film processing methods, tape coating methods and / or roll-to-roll manufacturing methods can be used when forming the quantum dot film of the present invention. The quantum dot combination dot composition can be directly applied to the desired layer of the substrate. Alternatively, the quantum dot composition can be formed as a solid layer of an independent element and then applied to the substrate. In some embodiments, the nanostructure composition can be deposited on one or more barrier layers.
[0283] Spin coating
[0284] In some embodiments, the nanostructure composition is deposited on a substrate using spin coating. In spin coating, a small amount of material is usually deposited on the center of a machine loaded with a substrate called a spin coater, which is fixed by a vacuum. High-speed rotation is applied to the substrate by the spin coater, which produces centrifugal force to diffuse the material from the center of the substrate to the edge. When most of the material is spun out, a certain amount of material is retained on the substrate, thereby continuing to form a film of material on the surface as the rotation continues. The final thickness of the film is determined by the properties of the deposited material and the substrate and the parameters (such as rotation speed, acceleration and rotation time) selected for the spin process. For typical films, a rotation speed of 1500-6000rpm and a rotation time of 10-60 seconds are used.
[0285] Fog deposition
[0286] In some embodiments, the nanostructure composition is deposited onto a substrate using mist deposition. Mist deposition is performed at room temperature and atmospheric pressure, and the film thickness is precisely controlled by changing process conditions. During the mist deposition process, the liquid source material becomes a very fine mist and is brought into the deposition chamber by nitrogen. The mist is then pulled to the wafer surface by the high voltage potential between the field screen and the wafer holder. Once the droplets are gathered on the wafer surface, the wafer is taken out of the chamber and thermally cured to evaporate the solvent. The liquid precursor is a mixture of a solvent and a material to be deposited. It is carried to the atomizer by pressurized nitrogen. Price, SC et al., "Formation of Ultra-Thin Quantum Dot Films by Mist Deposition," ESC Transactions 11: 89-94 (2007).
[0287] Spraying
[0288] In some embodiments, the nanostructured composition is deposited onto a substrate using spraying. Typical equipment for spraying includes a nozzle, an atomizer, a precursor solution, and a carrier gas. In the spray deposition method, the precursor solution is crushed into micro-sized droplets by a carrier gas or by atomization (e.g., ultrasound, air blast, or static electricity). The droplets coming out of the atomizer are accelerated by the substrate surface through the nozzle with the help of a carrier gas, and the carrier gas is controlled and regulated as required. The relative motion between the nozzle and the substrate is limited by design, and the purpose is to fully cover the substrate.
[0289] In some embodiments, the application of the nanostructure composition further comprises a solvent. In some embodiments, the solvent for applying the quantum dot composition is water, an organic solvent, an inorganic solvent, a halogenated organic solvent, or a mixture thereof. Exemplary solvents include, but are not limited to, water, D2O, acetone, ethanol, dioxane, ethyl acetate, methyl ethyl ketone, isopropanol, anisole, γ-butyrolactone, dimethylformamide, N-methylpyrrolidone, dimethylacetamide, hexamethylphosphoramide, toluene, dimethyl sulfoxide, cyclopentanone, tetramethylene sulfoxide, xylene, ε-caprolactone, tetrahydrofuran, tetrachloroethylene, chloroform, chlorobenzene, dichloromethane, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, or a mixture thereof.
[0290] In some embodiments, the composition is thermally cured to form the nanostructure layer. In some embodiments, the composition is cured using UV light. In some embodiments, the quantum dot composition is directly applied to the barrier layer of the quantum dot film, and then an additional barrier layer is deposited on the quantum dot layer to prepare the quantum dot film. In order to increase strength, stability and coating uniformity, and to prevent inconsistency of materials, bubble formation, and wrinkling or folding of barrier layer materials or other materials, a supporting substrate can be used below the barrier film. In addition, one or more barrier layers are preferably deposited on the quantum dot layer to seal the material between the top and bottom barrier layers. Suitably, the barrier layer can be deposited as a laminate film and optionally sealed or further processed, and then the nanostructure film is incorporated into a specific lighting device. As understood by those of ordinary skill in the art, the nanostructure composition deposition method may include additional or variable components. This embodiment will allow the nanostructure emission characteristics (e.g., brightness and color (e.g., to adjust the quantum film white point)) and the nanostructure film thickness and other characteristics of the online process adjustment. In addition, these embodiments will allow for periodic testing of quantum dot film properties during production, as well as any necessary switching to achieve precise nanostructure film properties. Such testing and adjustments can also be accomplished without changing the mechanical configuration of the process line, as a computer program can be employed to electronically change the respective amounts of the mixture used to form the nanostructure film.
[0291] Nanostructured membrane features and implementation schemes
[0292] In some embodiments, the nanostructured films of the present invention are used to form display devices. As used herein, a display device refers to any system having an illuminated display. Such devices include, but are not limited to, devices covering liquid crystal displays (LCDs), televisions, computers, mobile phones, smart phones, personal digital assistants (PDAs), gaming devices, electronic reading devices, digital cameras, and the like.
[0293] In some embodiments, the nanostructure film is part of a quantum dot color conversion layer.
[0294] In some embodiments, the display device comprises a quantum dot color converter. In some embodiments, the display device comprises a backplane; a display panel disposed on the backplane; and a quantum dot layer comprising the nanostructures. In some embodiments, the quantum dot layer is disposed on the display panel. In some embodiments, the quantum dot layer comprises a patterned quantum dot layer.
[0295] In some embodiments, the backplane includes a blue LED, LCD, OLED, or microLED.
[0296] In some embodiments, the display device comprises a quantum dot color converter. In some embodiments, the display device comprises a quantum dot layer comprising the nanostructure, and a light source element selected from blue LED, OLED, microLED and a combination thereof. In some embodiments, the quantum dot layer is disposed on the light source element. In some embodiments, the quantum dot layer comprises a patterned quantum dot layer. The patterned quantum dot layer can be prepared by any method known in the art. In one embodiment, the quantum dot layer is prepared by inkjet printing the quantum dot solution. Suitable solvents for the solution include, but are not limited to, dipropylene glycol monomethyl ether acetate (DPMA), poly glycidyl methacrylate (PGMA), diethylene glycol monoethyl ether acetate (EDGAC) and propylene glycol methyl ether acetate (PGMEA). Volatile solvents can also be used for inkjet printing because they allow rapid drying. Volatile solvents include ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate and tetrahydrofuran.
[0297] In some embodiments, the thickness of the quantum dot layer is from about 1 μm to about 25 μm. In some embodiments, the thickness of the quantum dot layer is from about 5 μm to about 25 μm. In some embodiments, the thickness of the quantum dot layer is from about 10 μm to about 12 μm.
[0298] In some embodiments, the optical film comprising the nanostructure composition is substantially free of cadmium. As used herein, the term "substantially free of cadmium" means that the nanostructure composition contains less than 100 ppm of cadmium by weight. The RoHS compliance definition requires that the weight percentage of cadmium in the original homogeneous precursor material does not exceed 0.01% (100 ppm). The cadmium concentration can be measured by inductively coupled plasma mass spectrometry (ICP-MS) analysis and is at the parts per billion (ppb) level. In some embodiments, the optical film "substantially free of cadmium" contains 10ppm-90ppm of cadmium. In other embodiments, the optical film substantially free of cadmium contains less than about 50ppm, less than about 20ppm, less than about 10ppm, or less than about 1ppm of cadmium.
[0299] Nanostructured Molded Products
[0300] In some embodiments, the present disclosure provides a nanostructured molded article comprising:
[0301] (a) a first barrier layer;
[0302] (b) a second barrier layer; and
[0303] (c) a nanostructure layer between the first barrier layer and the second barrier layer, wherein the nanostructure layer comprises a population of nanostructures comprising AIGS / AGS core-shell nanostructures, wherein the nanostructures have a PWL of 480-545, wherein at least about 80% of the emission is band edge emission, and exhibit a QY of 80-99.9%; and at least one organic resin.
[0304] In some embodiments, the present disclosure provides a nanostructured molded article comprising:
[0305] (a) a first barrier layer;
[0306] (b) a second barrier layer; and
[0307] (c) a nanostructure layer between the first barrier layer and the second barrier layer, wherein the nanostructure layer comprises a population of nanostructures comprising AIGS / AGS core-shell nanostructures, wherein the nanostructures have a PWL of 480-545, wherein at least about 80% of the emission is band-edge emission, and wherein the nanostructures exhibit a QY of 80-99.9%; and at least one organic resin.
[0308] In some embodiments, at least 80% of the emission is band edge emission. In other embodiments, at least 90% of the emission is band edge emission. In other embodiments, at least 95% of the emission is band edge emission. In some embodiments, 92-98% of the emission is band edge emission. In some embodiments, 93-96% of the emission is band edge emission. In another embodiment, the nanostructure is a quantum dot.
[0309] Barrier layer
[0310] In some embodiments, the nanostructured molding includes one or more barrier layers disposed on one or both sides of the nanostructured layer. Suitable barrier layers protect the nanostructured layer and the nanostructured molding from environmental conditions such as high temperature, oxygen and moisture. Suitable barrier materials include non-yellowing, transparent optical materials that are hydrophobic, chemically and mechanically compatible with the nanostructured molding, exhibit light stability and chemical stability and can withstand high temperatures. Preferably, one or more barrier layers are index matched with the nanostructured molding. In a preferred embodiment, the matrix material of the nanostructured molding and one or more adjacent barrier layers are index matched to have similar refractive indices so that most of the light that passes through the barrier layer toward the nanostructured molding is transmitted from the barrier layer into the nanostructured layer. This index matching reduces the light loss at the interface between the barrier layer and the matrix material.
[0311] The barrier layer is suitably a solid material and may be a solidified liquid, gel or polymer. Depending on the specific application, the barrier layer may include a flexible or non-flexible material. The barrier layer is preferably a planar layer and may include any suitable shape and surface area configuration, depending on the specific lighting application. In a preferred embodiment, one or more barrier layers will be compatible with lamination film processing technology, whereby the nanostructure layer is disposed on at least the first barrier layer, and at least the second barrier layer is disposed on the nanostructure layer on the opposite side of the nanostructure layer to form a nanostructure molded article according to an embodiment of the present invention. Suitable barrier materials include any suitable barrier materials known in the art. For example, suitable barrier materials include glass, polymers and oxides. Suitable barrier layer materials include, but are not limited to, polymers, such as polyethylene terephthalate (PET); oxides, such as silicon oxide, titanium oxide or aluminum oxide (e.g., SiO2, Si2O3, TiO2 or Al2O3); and suitable combinations thereof. Preferably, each barrier layer of the nanostructured molded article comprises at least 2 layers comprising different materials or compositions, so that the multi-layer barrier eliminates or reduces the pinhole defect arrangement in the barrier layer to provide an effective barrier to oxygen and moisture penetration into the nanostructured layer. The nanostructured layer may include any suitable material or combination of materials and any suitable number of barrier layers on either or both sides of the nanostructured layer. The material, thickness and number of barrier layers will depend on the specific application and will be appropriately selected to maximize the barrier protection and brightness of the nanostructured layer while minimizing the thickness of the nanostructured molded article. In a preferred embodiment, each barrier layer comprises a laminated film, preferably a double-layer laminated film, wherein the thickness of each barrier layer is thick enough to eliminate wrinkling in a roll-to-roll or lamination manufacturing process. In an embodiment where the nanostructure comprises heavy metals or other toxic materials, the number or thickness of the barrier layers may further depend on statutory toxicity guidelines, which may require more or thicker barrier layers. Other considerations for blocking include cost, availability and mechanical strength.
[0312] In some embodiments, the nanostructured film includes two or more barrier layers adjacent to each side of the nanostructured layer, for example, two or three layers on each side of the nanostructured layer or two barrier layers on each side of the nanostructured layer. In some embodiments, each barrier layer comprises a thin glass sheet, for example, a glass sheet having a thickness of about 100 μm, 100 μm or less, or 50 μm or less.
[0313] Each barrier layer of the nanostructured film of the present invention can have any suitable thickness, which will depend on the specific requirements and characteristics of the lighting device and application, as well as the individual film components, such as the barrier layer and the nanostructure layer, as will be understood by a person of ordinary skill in the art. In some embodiments, the thickness of each barrier layer can be 50 μm or less, 40 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, or 15 μm or less. In certain embodiments, the barrier layer comprises an oxide coating, which may include materials such as silicon oxide, titanium oxide, and aluminum oxide (e.g., SiO2, Si2O3, TiO2, or Al2O3). The thickness of the oxide coating may be about 10 μm or less, 5 μm or less, 1 μm or less, or 100 nm or less. In certain embodiments, the barrier layer comprises a thin oxide coating having a thickness of about 100 nm or less, 10 nm or less, 5 nm or less, or 3 nm or less. The top and / or bottom barrier layer may consist of a thin oxide coating, or may include a thin oxide coating and one or more additional layers of material.
[0314] Display device with nanostructured color conversion layer
[0315] In some embodiments, the present invention provides a display device comprising:
[0316] (a) a display panel, which is used to emit a first light;
[0317] (b) a backlight unit configured to provide the first light to the display panel; and
[0318] (c) A color filter including at least one pixel region including a color conversion layer.
[0319] In some embodiments, the color filter includes at least 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 pixel regions. In some embodiments, when blue light is incident on the color filter, red light, white light, green light, and / or blue light can be emitted through the pixel regions, respectively. In some embodiments, the color filter is described in U.S. Patent No. 9,971,076, which is incorporated herein by reference in its entirety.
[0320] In some embodiments, each pixel region includes a color conversion layer. In some embodiments, the color conversion layer comprises nanostructures described herein that are configured to convert incident light into light of a first color. In some embodiments, the color conversion layer comprises nanostructures described herein that are configured to convert incident light into blue light.
[0321] In some embodiments, the display device comprises 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 color conversion layers. In some embodiments, the display device comprises 1 color conversion layer comprising the nanostructures described herein. In some embodiments, the display device comprises 2 color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises 3 color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises 4 color conversion layers comprising the nanostructures described herein. In some embodiments, the display device comprises at least one red conversion layer, at least one green conversion layer and at least one blue conversion layer.
[0322] In some embodiments, the color conversion layer has a thickness of about 3 μm to about 10 μm, about 3 μm to about 8 μm, about 3 μm to about 6 μm, about 6 μm to about 10 μm, about 6 μm to about 8 μm, or about 8 μm to about 10 μm. In some embodiments, the color conversion layer has a thickness of about 3 μm to about 10 μm.
[0323] The nanostructure color conversion layer can be deposited by any suitable method known in the art, including but not limited to painting, spraying, solvent spraying, wet coating, adhesive coating, spin coating, tape coating, roller coating, flow coating, inkjet printing, photoresist patterning, drop casting, blade coating, mist deposition or a combination thereof. In some embodiments, the nanostructure color conversion layer is deposited by photoresist patterning. In some embodiments, the nanostructure color conversion layer is deposited by inkjet printing.
[0324] AIGS / AGS core-shell nanostructures with silane ligands
[0325] In some embodiments, the AIGS / AGS core-shell nanostructure further comprises a silane ligand. In some embodiments, the silane ligand is an aminoalkyltrialkoxysilane or a mercaptoalkyltrialkoxysilane. Non-limiting examples of aminoalkyltrialkoxysilanes include 3-aminopropyl(trimethoxysilane), 3-aminopropyl(triethoxysilane), 3-aminopropyl(diethoxymethoxysilane), 3-aminopropyl(tripropoxysilane), 3-aminopropyl(dipropoxymethoxysilane), 3-aminopropyl(tri-dodecyloxysilane), 3-aminopropyl(tri-tetradecyloxysilane), 3-aminopropyl(tri-hexadecyloxysilane), 3-aminopropyl(tri-octadecyloxysilane), 3-aminopropyl(di-dodecyloxy)tetradecyloxysilane, 3-aminopropyl(dodecyloxy)tetradecyloxy(hexadecyloxy)-silane, 3-aminopropyl(dimethoxy 3-aminopropyl(diisopropoxymethylsilane), 3-aminopropyl(isopropoxydimethylsilane), 3-aminopropyl(dibutoxymethylsilane), 3-aminopropyl(butoxydimethylsilane), 3-aminopropyl(diisobutoxymethylsilane), 3-aminopropyl(isobutoxydimethylsilane), 3-aminopropyl(di-dodecyloxymethylsilane 2-aminoethyl(trimethoxysilane), 2-aminoethyl(triethoxysilane), 2-aminoethyl(diethoxymethoxysilane), 2-aminoethyl(tripropoxysilane), 2-aminoethyl(tripropoxymethoxysilane), 2-aminoethyl(tri-dodecyloxysilane), 2-aminoethyl(tri-tetradecyloxysilane), 2-aminoethyl(tri-hexadecyloxysilane), 2-aminoethyl(tri-octadecyloxysilane), 2-aminoethyl(di-dodecyloxy)tetradecyl Alkoxysilane, 2-aminoethyl(dodecyloxy)tetradecyloxy(hexadecyloxy)silane, 2-aminoethyl(dimethoxymethylsilane), 2-aminoethyl(methoxydimethylsilane), 2-aminoethyl(diethoxymethylsilane), 2-aminoethyl(ethoxydimethylsilane), 1-aminomethyl(trimethoxysilane), 1-aminomethyl(triethoxysilane), 1-aminomethyl(diethoxymethoxysilane), 1-aminomethyl(dipropoxymethoxysilane), 1-aminomethyl(tripropoxysilane), 1-aminomethyl(trimethoxysilane), 1-aminomethyl(dimethoxymethylsilane), 1-aminomethyl(methoxydimethylsilane),1-aminomethyl (diethoxymethylsilane), 1-aminomethyl (ethoxydimethylsilane), 3-aminobutyl (trimethoxysilane), 3-aminobutyl (triethoxysilane), 3-aminobutyl (diethoxymethoxysilane), 3-aminobutyl (tripropoxysilane), 3-aminobutyl (dipropoxymethoxysilane), 3-aminobutyl (dimethoxymethylsilane), 3-aminobutyl (diethoxymethylsilane), 3-aminobutyl (dimethylmethoxysilane), 3-aminobutyl (dimethylethoxysilane), 3-aminobutyl (tri-dodecyloxysilane), 3-aminobutyl (tri-tetradecyloxysilane), 3-aminobutyl (tri- Hexadecyloxysilane), 3-aminobutyl (di-dodecyloxy) tetradecyloxysilane, 3-aminobutyl (dodecyloxy) tetradecyloxy (hexadecyloxy) silane, 3-amino-2-methylpropyl (trimethoxysilane), 3-amino-2-methylpropyl (triethoxysilane), 3-amino-2-methylpropyl (diethoxymethoxysilane), 3-amino-2-methylpropyl (tripropoxysilane), 3-amino-2-methylpropyl (dipropoxymethoxysilane), 3-amino-2-methylpropyl (tri-dodecyloxysilane), 3-amino-2-methylpropyl (tri-tetradecyloxysilane), 3-amino-2-methylpropyl (tri-hexadecyloxysilane Alkoxysilane), 3-amino-2-methylpropyl (tri-octadecyloxysilane), 3-amino-2-methylpropyl (di-dodecyloxy) tetradecyloxysilane, 3-amino-2-methylpropyl (dodecyloxy) tetradecyloxy-(hexadecyloxy) silane, 3-amino-2-methylpropyl (dimethoxymethylsilane), 3-amino-2-methylpropyl (methoxydimethylsilane), 3-mercapto-2-methylpropyl (diethoxymethylsilane), 3-mercapto-2-methylpropyl (ethoxydimethylsilane), 3-mercapto-2-methylpropyl (dipropoxymethylsilane), 3-amino-2-methylpropyl (propoxydimethylsilane), 3-amino -2-methylpropyl (diisopropoxymethylsilane), 3-amino-2-methylpropyl (isopropoxydimethylsilane), 3-amino-2-methylpropyl (dibutoxymethylsilane), 3-amino-2-methylpropyl (butoxydimethylsilane), 3-amino-2-methylpropyl (diisobutoxymethylsilane), 3-amino-2-methylpropyl (isobutoxydimethylsilane), 3-amino-2-methylpropyl (didodecyloxymethylsilane), 3-amino-2-methylpropyl (dodecyloxydimethylsilane), 3-amino-2-methylpropyl (di-tetradecyloxymethylsilane) and 3-amino-2-methylpropyl (tetradecyloxydimethylsilane).
[0326] Non-limiting examples of mercaptoalkyltrialkoxysilanes include 1-mercaptomethyltriethoxysilane, 1-mercaptoethyltrimethoxysilane, 1-mercaptoethyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, 3-mercapto-1-propyltrimethoxysilane, 3-mercapto-1-propyltriethoxysilane, 3-mercapto-1-propylmethyldimethoxysilane, 3-mercapto-1-propylmethyldieth ... Methylethoxysilane, 3-mercapto-1-propyldimethylmethoxysilane, 3-mercapto-1-propyltripropoxysilane, 3-mercapto-1-propyltriisopropoxysilane, 3-mercapto-1-propyltributoxysilane, 8-mercapto-1-octyltrimethoxysilane, 8-mercapto-1-octyltriethoxysilane, 10-mercapto-1-decyltriethoxysilane, 10-mercapto-1-decyltrimethoxysilane, mercaptomethyltriethoxysilane and mercaptomethyltrimethoxysilane.
[0327] AIGS / AGS core-shell nanostructures with aminoalkyltrialkoxysilane ligands adhere more strongly to glass than when using polyethylene glycol-containing ligands. Thus, AIGS / AGS-silane ligands are particularly suitable for quantum dot color conversion layers.
[0328] The following examples are illustrative and non-limiting of the products and methods described in this patent. Suitable modifications and adjustments of various conditions, formulations and other parameters commonly encountered in the art and modifications and adjustments that are obvious to those skilled in the art in view of this disclosure are all within the spirit and scope of the present invention.
[0329] Example
[0330] Example 1: AIGS nucleosynthesis
[0331] Sample ID 1 was prepared using a typical synthesis of the AIGS core as follows: 4 mL of 0.06 M CH3CO2Ag oleylamine solution, 1 mL of 0.2 M InCl3 ethanol solution, 1 mL of 0.95 M sulfur in oleylamine solution and 0.5 mL of dodecanethiol were injected into a flask containing 5 mL of degassed octadecene, 300 mg of trioctylphosphine oxide and 170 mg of gallium acetylacetonate. The mixture was heated to 40°C and maintained for 5 minutes, and then the temperature was increased to 210°C and maintained for 100 minutes. After cooling to 180°C, 5 mL of trioctylphosphine was added. The reaction mixture was transferred to a glove box and diluted with 5 mL of toluene. The final AIGS product was precipitated by adding 75 mL of ethanol, centrifuged and redispersed in toluene. Samples ID 2 and 3 were also prepared using this method. Measurement of the optical properties of the AIGS cores as shown in Figure 1A and 1BThe AIGS core size and morphology were characterized by transmission electron microscopy (TEM). Figure 2 shown.
[0332] Table 1
[0333]
[0334] Example 2: AIGS / AGS core / shell synthesis
[0335] Sample ID 4 was prepared using the following typical synthesis of AIGS / AGS core / shell: 2 mL of 0.3 M gallium oleate in octadecene and 12 mL of oleylamine were added to a flask and degassed. The mixture was heated to 270°C. A premixed solution of 1 mL of 0.95 M sulfur in oleylamine and 1 mL of isolated AIGS cores (15 mg / mL) were co-injected. Shell growth stopped after 30 minutes. The final core / shell product was transferred to a glove box, washed with toluene / ethanol, centrifuged, and redispersed in toluene. Samples ID 4-8 were also prepared using this method. The optical properties of the AIGS / AGS core / shell materials are shown in Figure 2. Figure 3 The growth of the shell leads to almost complete band-edge emission. The increase in the average particle size after shell growth was observed by TEM, as shown in Table 2. Figure 4 shown.
[0336] Table 2
[0337]
[0338] Example 3: Gallium halide and trioctylphosphine surface treatment
[0339] Room temperature surface modification of AIGS was performed by adding trioctylphosphine solution (0.01-0.25 M) of GaI3 to AIGS QDs and keeping them at room temperature for 20 h. This treatment resulted in a significant enhancement of the band edge emission, such as Figure 5A and 5B As shown and summarized in Table 3, while substantially maintaining the peak wavelength (PWL). Therefore, the present invention solves the problem of red-shifted band edge emission observed with prior art methods (Uematsu et al., NPG Asia Materials 10:713-726 (2018); Kameyama et al., ACS Appl. Mater. Interfaces 10:42844-42855 (2018)).
[0340] The composition changes before and after the addition of GaI3 were monitored by inductively coupled plasma atomic emission spectroscopy (ICP-AES) and energy dispersive X-ray spectroscopy (EDS), as summarized in Table 3. The composite images of the In and Ga elemental distributions before and after the GaI3 / TOP surface treatment show the radial distribution of In relative to Ga.
[0341] Table 3
[0342]
[0343] Example 4: Synthesis of AIGS / AGS core / shell using oxygen-free Ga source
[0344] Sample IDs 14 and 15 were prepared using the following typical synthesis of AIGS / AGS core / shell using an oxygen-free Ga source: 400 mg GaCl3 dissolved in 400 μL toluene was added to 8 mL of degassed oleylamine, followed by 40 mg of AIGS core and then 1.7 mL of 0.95 M sulfur in oleylamine. After heating to 240°C, the reaction was maintained for 2 hours and then cooled. The final core / shell product was transferred to a glove box, washed with toluene / ethanol, centrifuged and dispersed in toluene. Sample IDs 15 and 16 were also prepared using this method. Sample IDs 11-13 were prepared using the method of Example 2. The optical properties of the AIGS / AGS core / shell materials are shown in Table 4.
[0345] Table 4
[0346]
[0347] As shown in Table 4, when oleylamine is used as the solvent, the quantum yield of the AIGS / GS core / shell material can be improved by using Ga(III) chloride instead of Ga(III) acetylacetonate or Ga(III) oleate. Fig. 6A and 6B The sizes of the final core / shell materials were compared and it was shown that the core / shell materials prepared using Ga(III) chloride had similar sizes and similar band edge and trap emission properties. Therefore, the increase in quantum yield (QY) is not simply due to an increased trap emission component. And, unexpectedly, it was found that when Ga(III) iodide was used instead of Ga(III) chloride, the AIGS core seemed to dissolve in the reaction mixture and no shell formation occurred.
[0348] High-resolution TEM with energy dispersive X-ray spectroscopy (EDS) of sample 14 shows that the shell is better described as a gradient from an AIGS core to an AGS shell, suggesting that the shell formation under these conditions results from the incorporation of Ag into the shell rather than the growth of a distinct thick GS layer. This may also contribute to the improved quantum yield of the nanostructures because of the smaller strain from the shell.
[0349] Example 5: AIGS cores from hot injection of preformed Ag2S nanostructures mixed with preformed In-Ga reagents
[0350] To prepare Ag2S nanostructures, 0.5 g of AgI and 2 mL of oleylamine were added to a 20 mL vial under N2 atmosphere and stirred at 58°C until a clear solution was obtained. In a separate 20 mL vial, 5 mL of DDT and 9 mL of 0.95 M sulfur in oleylamine solution were mixed. The DDT+S-OYA mixture was added to the AgI solution and stirred at 58°C for 10 minutes. The obtained Ag2S nanoparticles were used without washing.
[0351] To prepare the In-Ga reagent mixture, 1.2 g Ga(acetylacetonate)3, 0.35 g InCl3, 2.5 mL oleylamine and 2.5 mL ODE were placed in a 100 mL flask. Heat to 210 °C under N2 atm and hold for 10 minutes. An orange viscous product was obtained.
[0352] To form AIGS nanoparticles, 1.75 g of TOPO, 23 mL of oleylamine and 25 mL of L ODE were added to a 250 mL flask under N2. After degassing under vacuum, the solvent mixture was heated to 210 ° C for 40 minutes. In a 40 mL vial, the Ag2S and In-Ga reagent mixtures from the above were mixed at 58 ° C and transferred to a syringe. The Ag-In-Ga mixture was then injected into the solvent mixture at 210 ° C and kept for 3 hours. After cooling to 180 ° C, 5 mL of trioctylphosphine was added. The reaction mixture was transferred to a glove box and diluted with 50 mL of toluene. The final product was precipitated by adding 150 mL of ethanol, centrifuged and redispersed in toluene. This core was shelled by the method described in Example 4. The optical properties of the core / shell material prepared by this method scaled up to 24 times are shown in Table 5.
[0353] Table 5
[0354]
[0355] As shown in Table 5, using the method of pre-forming some of the reaction components of AIGS and then injecting them into the hot solvent mixture, both the band edge emission percentage and the quantum yield are unexpectedly improved.
[0356] Example 6 - AIGS / AGS Nanostructures with Silane Ligands
[0357] The AIGS / GS core-shell nanostructures were reacted with a mixture of Jeffamine and (3-aminopropyl)trimethoxysilane (APTMS) to obtain a silane ligand complex. As shown in Table 6, the ligand-containing AIGS / AGS nanostructures retained about 76% of their QY.
[0358] Table 6
[0359] QD Type QY AIGS / AGS 76.9% AIGS / AGS with Jeffamine / APTMS 76.3%
[0360] Although various embodiments have been described above, it should be understood that they are presented by way of example only and not limitation. It will be apparent to those skilled in the relevant art that various changes may be made in form and detail without departing from the spirit and scope of the invention. Therefore, the breadth and scope should not be limited by any of the above exemplary embodiments, but should be defined only in accordance with the following claims and their equivalents.
[0361] All publications, patents, and patent applications mentioned in this specification are indicative of the levels of skill of those skilled in the art to which this invention pertains and are herein incorporated by reference to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference.
Claims
1. A quantum dot comprising Ag, In, Ga and S (AIGS) having a gradient from an AIGS core to an AGS without a distinct GS layer, wherein the peak emission wavelength (PWL) of the quantum dot is in the range of 480-545 nm and wherein at least 80% of the emission is band edge emission, and wherein the quantum dot exhibits a quantum yield (QY) of 80-99.9%, and wherein the quantum dot further comprises a ligand bound to the quantum dot, wherein the quantum dots are prepared by a method comprising: (a) preparing a mixture comprising Ag-In-Ga-S (AIGS) cores, a sulfur source, a ligand and gallium chloride at 180-300° C.; (b) maintaining the mixture at a temperature in the range of 180-300° C. for 5-300 minutes; and (c) isolating the quantum dots, wherein the ratio of gallium chloride to AIGS core is 0.008-0.2 mmol of gallium chloride / mgAIGS; or The quantum dots are prepared by a method comprising: (a) reacting Ga(acetylacetone)3, InCl3 and a ligand optionally in a solvent at a temperature sufficient to obtain an In-Ga reagent, and (b) reacting the In-Ga reagent with an Ag2S nanostructure at a temperature sufficient to form AIGS quantum dots, and (c) reacting the AIGS quantum dots with an oxygen-free Ga salt in a solvent containing a ligand at a temperature sufficient to form AIGS / AGS core-shell quantum dots, wherein the sufficient temperature in (a) is 100-280°C; the sufficient temperature in (b) is 150-260°C; and the sufficient temperature in (c) is 170-280°C. The quantum dot according to claim 1 , wherein the ligand is a silane. The quantum dot according to claim 2 , wherein the silane is an aminoalkyltrialkoxysilane. The quantum dot according to claim 3 , wherein the aminoalkyltrialkoxysilane is (3-aminopropyl)triethoxysilane. The quantum dot according to claim 2 , wherein the silane is a mercaptoalkyltrialkoxysilane. The quantum dot according to claim 5 , wherein the mercaptoalkyltrialkoxysilane is 3-mercaptopropyltrimethoxysilane.
7. The quantum dots according to any one of claims 1 to 6, adhered to a substrate. The quantum dots according to claim 7 , wherein the substrate is glass.
9. The quantum dot of claim 8, wherein the glass is part of a quantum dot color converter.
10. The quantum dot according to claim 9, wherein the quantum dot color converter comprises Back panel; A display panel is disposed on the back panel; and A quantum dot layer comprising the quantum dots is disposed on the display panel. The quantum dot of claim 10 , wherein the quantum dot layer comprises a patterned quantum dot layer.
12. The quantum dots of claim 10, wherein the backplane comprises an LED, an LCD, an OLED, or a microLED.
13. A display device comprising The display panel is configured to emit a first light; a backlight panel configured to provide the first light to the display panel; and A color filter comprising at least one pixel region comprising a color conversion layer, wherein the color conversion layer comprises quantum dots comprising Ag, In, Ga and S (AIGS), the quantum dots having a gradient from an AIGS core to an AGS without a significant GS layer, wherein the peak emission wavelength (PWL) of the quantum dots is in the range of 480-545 nm and wherein at least 80% of the emission is band edge emission, and wherein the quantum dots exhibit a quantum yield (QY) of 80-99.9%, wherein the quantum dots are the quantum dots according to any one of claims 1-12. 14 . The display device according to claim 13 , wherein the color conversion layer has a thickness of 3 μm to 10 μm.
15. The display device of claim 13, wherein the backplane comprises LED, LCD, OLED or microLED.
Citation Information
Patent Citations
Compositions and methods for modulation of nanostructure energy levels
US20080118755A1
Highly luminescent nanostructures and methods of producing same
US20150236195A1
Preparation of III-V semiconductor nanocrystals
US5505928A
Process for forming shaped group III-V semiconductor nanocrystals, and product formed using process
US6306736B1
Preparation of nanocrystallites
US6576291B2